A leukocyte activation test identifies food items which induce release of DNA by innate immune peripheral blood leucocytes - Garcia-Martinez, Irma (Nutr Metab (Lond), 2018)
BACKGROUND: Leukocyte activation (LA) testing identifies food items that induce a patient specific cellular response in the immune system, and has recently been shown in a randomized double blinded prospective study to reduce symptoms in patients with irritable bowel syndrome (IBS). We hypothesized that test reactivity to particular food items, and the systemic immune response initiated by these food items, is due to the release of cellular DNA from blood immune cells. METHODS: We tested this by quantifying total DNA concentration in the cellular supernatant of immune cells exposed to positive and negative foods from 20 healthy volunteers. To establish if the DNA release by positive samples is a specific phenomenon, we quantified myeloperoxidase (MPO) in cellular supernatants. We further assessed if a particular immune cell population (neutrophils, eosinophils, and basophils) was activated by the positive food items by flow cytometry analysis. To identify the signaling pathways that are required for DNA release we tested if specific inhibitors of key signaling pathways could block DNA release. RESULTS: Foods with a positive LA test result gave a higher supernatant DNA content when compared to foods with a negative result. This was specific as MPO levels were not increased by foods with a positive LA test. Protein kinase C (PKC) inhibitors resulted in inhibition of positive food stimulated DNA release. Positive foods resulted in CD63 levels greater than negative foods in eosinophils in 76.5% of tests. CONCLUSION: LA test identifies food items that result in release of DNA and activation of peripheral blood innate immune cells in a PKC dependent manner, suggesting that this LA test identifies food items that result in release of inflammatory markers and activation of innate immune cells. This may be the basis for the improvement in symptoms in IBS patients who followed an LA test guided diet. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12986-018-0260-4) contains supplementary material, which is available to authorized users.